Differences in lactate exchange and removal abilities between high-level African and Caucasian 400-m track runners - Bret, C.; Lacour, J.-R.; Bourdin, M.; Locatelli, E.; de Angelis, M.; Faina, M.; Rahmani, A.; Messonnier, L. (European Journal of Applied Physiology, 2013)
The present study aimed to investigate (1) whether high-level 400-m track runners of different ethnic origin displayed divergent post-run blood lactate concentrations (p400m[La]) and (2) if this discrepancy was based on differences in lactate exchange and removal abilities. Twenty male African (n = 12) and Caucasian (n = 8) runners, paired in terms of personal record, performed (1) an all-out 400-m run to measure p400m[La] at 3, 5 and 7 min into recovery and (2) a 1-min 25.2 km/h running (not maximal but standardized) exercise followed by 90-min passive recovery to determine individual blood lactate recovery curves (IBLRC). IBLRCs were fitted to a bi-exponential time function: La(t)=La(0)+A1(1-e-y1t)+A2(1-e-y2t) where y1 and y2 denote lactate exchange ability between the previously worked muscles and blood, and overall ability for lactate removal, respectively. The quantity of lactate accumulated at the end of the 1-min exercise (Q LaA) was also estimated. Our study showed that after the all-out 400-m run, p400m[La] was lower in African than in Caucasian runners at 3 and 5 min but not at 7 min into recovery. After the standardized exercise, y1 and y2 were lower (p < 0.01) and Q LaA was higher (p < 0.05) in African than in Caucasian runners. These data suggest that for similar performance levels, ethnicity involves differences in lactate accumulation, exchange and removal.